2015
DOI: 10.1038/npp.2015.90
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Brain Atrophy and Cortical Thinning in Schizophrenia after Commencing Clozapine Treatment

Abstract: Despite evidence that clozapine may be neuroprotective, there are few longitudinal magnetic resonance imaging (MRI) studies that have specifically explored an association between commencement of clozapine treatment for schizophrenia and changes in regional brain volume or cortical thickness. A total of 33 patients with treatment-resistant schizophrenia and 31 healthy controls matched for age and gender underwent structural MRI brain scans at baseline and 6-9 months after commencing clozapine. MRI images were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
2
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 47 publications
8
51
2
5
Order By: Relevance
“…Furthermore, brain volumetric changes do not seem to correlate with poor clinical response or outcomes. In patients treated with clozapine, both a grey matter decrement and a clinical improvement have been reported, whereas in other studies the opposite was found.…”
Section: Brain Structure and Functioningmentioning
confidence: 84%
“…Furthermore, brain volumetric changes do not seem to correlate with poor clinical response or outcomes. In patients treated with clozapine, both a grey matter decrement and a clinical improvement have been reported, whereas in other studies the opposite was found.…”
Section: Brain Structure and Functioningmentioning
confidence: 84%
“…However, as discussed above, changes in gyrification have been related to early cortical development, so that the gyrification changes are more likely to precede the onset of the migraine, representing a promising candidate to predict response to treatment. In contrast, CT changes are much more dynamic over time, and previous studies have examined potential effects of environmental factors, experience‐related plasticity, and intake of psychotropic medication . While there are fewer data on the effect of simple analgesic on brain structure, studies in rat models have demonstrated effect of opioids on synaptic structure, and effects of triptans on brain connectivity .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CT changes are much more dynamic over time, 22 and previous studies have examined potential effects of environmental factors, 47 experience-related plasticity, 48,49 and intake of psychotropic medication. [50][51][52] While there are fewer data on the effect of simple analgesic on brain structure, studies in rat models have demonstrated effect of opioids on synaptic structure, 53 and effects of triptans on brain connectivity. 54 These data in mouse models thus leave open the possibility that medication overuse alters CT, requiring the need for further longitudinal studies to better understand whether the observed altered thickness causes medication overuse or results from it.…”
Section: Discussionmentioning
confidence: 99%
“…cerebral cortex) volumes have been previously reported in rodents in which the duration of antipsychotic treatment varied from 1 to 2 months(Vernon et al, 2011) and in large cohorts of patients with schizophrenia(Haijma et al, 2013). On the other hand, evidence is emerging that gray matter loss in schizophrenia reflects the underlying disease process irrespective of clozapine treatment(Ahmed et al, 2015; Anderson et al, 2015). Therefore, the lack of frontal lobe volume changes in the clozapine-treated monkeys of the present study could also be explained, in part, by the absence of the underlying disease process (schizophrenia) in the animals.…”
Section: Discussionmentioning
confidence: 99%